PULMONARY EMBOLISM: A COMPLICATION OF COVID -19 INFECTION IN POSTPARTUM – CASE REPORT - Stojanoska, Tatjana; Cvetanovska, Marija; Demiri, Ilir; Stevanovic, Milena; Saveski, Velimir; Ridova, Nevenka; Kadriu, Romir (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
It has been proposed that pregnant women and their fetuses may be particularly at risk for poor outcomes due to the coronavirus pandemic. A 28-year old women in early postpartum period after Caesarian delivery presented with a five-day history of malaise, bone and muscle pains, dry cough, fever and dyspnea. A nasopharyngeal swab was positive for SARS-CoV-2. Laboratory findings confirmed increased inflammatory markers. Her condition rapidly worsened after delivery, leading to a severe respiratory failure, low oxygen saturation and the need of non-invasive ventilation.   What was the most notable from laboratory follow-ups was marked elevation of fibrin degradation products, despite anticoagulation prophylaxis. We immediately performed CT angiography, which showed thromboembolism. Subsequently, anticoagulant therapy doses were increased up to therapeutic doses and additional antithrombotic therapy was initiated. Ten days later, she was discharged in a good clinical condition, oxygen-free, with normal auscultatory findings and laboratory analyses within reference ranges. The purpose of this case report is to draw attention to probably one of the most life-threatening and severe complications of COVID-19, which is the thrombogenic component of the infection, appealing toregular monitoring of haemostasis and predictive laboratory markers of inflammation. This may alleviate or prevent the occurrence of cytokine storm and to direct the therapeutic approach, emphasizing the need of adequate doses of anticoagulant therapy, with special consideration to the most vulnerable group of patients â€“gravid patients and new mothers in early postpartum period. Keywords: COVID- 19, thromboembolism, post-partum complications. https://doi.org/10.55302/JMS2143126s